Current Pattern and Diagnosis of Small Bowel Obstruction in the Patients of Rural Areas (Medical Forum Monthly, 2024)
Objective: Objective of this study to determine the clinical presenting factors including diagnosis and risk factors of the patients those admitted with small bowel obstruction.Study Design: Observational studyPlace and Duration of Study: This study was carried out at the Departments of General Surgery, Peoples Medical University and Health Science Nawabshah and Isra University Hospital Hyderabad from March 2013 to Aug 2013.Materials and Methods: After admission detailed history, physical examination, ultrasound, X-ray abdomen erect and supine and all routine baseline laboratory investigations were carried out. CT scan was done in the selected patients. Final diagnosis was done by laparotomy which was attempted after thorough initial assessment and investigations.Results: Total 50 patients were included in the study of the rural areas of the Sindh, from all of them male were in majority. On the clinical presenting features Nausea, Constipation and Abdominal pain were most common with the percentage of 92%, 80% and 78% while other presenting features as; Vomiting, Abdominal tenderness, Abdominal distension, Fever, Epigastrium pain, Rectal bleeding and Rebound tenderness were with the percentage of 40%, 42%, 22%, 38%, 30%, 16%, 10% and 26% respectively. On the diagnosis adhesion was found as most common.Conclusions: In the conclusion of this study adhesion found as most common and leading cause of small bowel obstruction.